The Missing Link between Trade, Industrial, Agriculture, and Climate Change in African Policy and Strategies’ Design, Formulation and Implementation - (:unkn) unknown (My University, 2024)
In today’s rapidly changing world, the significance of accurate weather forecasts cannot be overstated. Trade, industrial, agriculture, and climate change policies and strategies play a crucial role in shaping the development trajectory of countries and regions. They can significantly impact economic growth, food security, and environmental sustainability. The objectives of this paper are to identify the existing gaps in the design, formulation, and implementation of trade, industrial, agriculture, and climate change policies and strategies in Africa, to explore the relationship between these policy areas and their impact on sustainable development, and to provide recommendations for more integrated and effective policies and strategies. This paper’s methodology involves reviewing and analysing existing trade, industrial, agriculture, and climate change policies and strategies in Africa. The literature review reveals a lack of comprehensive and coherent policies and strategies addressing Africa’s trade, industry, agriculture, and climate change linkages. Existing policies and strategies focus on individual sectors in isolation rather than a holistic and integrated approach.Furthermore, the literature highlights a lack of recognition of the gender-differentiated roles in agriculture and the gender-differentiated impacts of climate change. The paper recommends that African countries develop comprehensive and integrated policies and strategies that recognise the interlinkages between trade, industry, agriculture, and climate change. These policies and strategies should take a holistic approach, considering the potential synergies and trade-offs between these sectors and incorporating climate change considerations. Second, there is a need to mainstream gender into these policies and strategies. This can be done by recognising and addressing the gender-differentiated roles in agriculture and the gender-differentiated impacts of climate change.
Keywords: African Research